Laser Lap Joining of Dissimilar Materials: A Review of Factors Affecting Joint Strength - Tamrin, K. F.; Nukman, Y.; Zakariyah, S.S. (Taylor & Francis Ltd, 2013)
Laser joining of dissimilar materials has been the subject of intensive studies in the past decade or thereabout. This is mainly due to the several benefits it offers when used to manufacture various electromechanical components for automotive, aerospace, electronics, and biomedical applications. There are many possible variations of joining dissimilar materials; this article, however, considers the main engineering materials in use today, namely, metal, polymer, ceramic, glass, and silicon. The strength of the joints determined by, inter alia, the material combinations, joining technique, and material treatment is crucial for the above mentioned applications if safety and reliability requirements are to be adhered to. Undoubtedly, the challenges posed by such complex selection of materials and process factors are unquantifiable and as such have been given a critical review in this article. The relationship between some important laser processing parameters and joint strength are also discussed. Furthermore, it has been observed that the joint strength can also be influenced by factors such as bubbles morphology, material preparation/treatment, depth of molten pool and formation of chemical bonds, and intermetallic phases and their effects are also reviewed and discussed. This article is concluded with an outlook providing the summary and key findings of the authors.